2021
DOI: 10.1002/aws2.1249
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical technologies for per‐ and polyfluoroalkyl substances mitigation in drinking water and water treatment residuals

Abstract: Water treatment technologies are needed that can convert per-and polyfluoroalkyl substances (PFAS) into inorganic products (e.g., CO 2 , F À ) that are less toxic than parent PFAS compounds. Research on electrochemical treatment processes such as electrocoagulation and electrooxidation has demonstrated proof-of-concept PFAS removal and destruction. However, research has primarily been conducted in laboratory matrices that are electrochemically favorable (e.g., high initial PFAS concentration [μg/L-mg/L], high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…EC has the ability to eliminate PFAS through either non-destructive phase separation or destructive oxidative pathways. Compared to other PFAS treatment methods that are destructive, such as sonolysis, ultraviolet (UV) advanced oxidation, advanced reduction, and photocatalysis, EC requires less energy input [105]. Most studies using EC to remove PFAS have concentrated on non-destructive methods that involve the sorption of PFAS to metal hydroxide flocs created using sacrificial electrodes [105].…”
Section: Removal Of Pfassmentioning
confidence: 99%
See 2 more Smart Citations
“…EC has the ability to eliminate PFAS through either non-destructive phase separation or destructive oxidative pathways. Compared to other PFAS treatment methods that are destructive, such as sonolysis, ultraviolet (UV) advanced oxidation, advanced reduction, and photocatalysis, EC requires less energy input [105]. Most studies using EC to remove PFAS have concentrated on non-destructive methods that involve the sorption of PFAS to metal hydroxide flocs created using sacrificial electrodes [105].…”
Section: Removal Of Pfassmentioning
confidence: 99%
“…Compared to other PFAS treatment methods that are destructive, such as sonolysis, ultraviolet (UV) advanced oxidation, advanced reduction, and photocatalysis, EC requires less energy input [105]. Most studies using EC to remove PFAS have concentrated on non-destructive methods that involve the sorption of PFAS to metal hydroxide flocs created using sacrificial electrodes [105]. Iron and aluminum are the commonly used electrodes, while zinc has shown greater PFOA removal compared to iron and aluminum [106].…”
Section: Removal Of Pfassmentioning
confidence: 99%
See 1 more Smart Citation
“…The issues with membrane retentate streams also apply to other hard‐to‐treat waters such as landfill leachates, remediation waters, and wastewaters. To identify approaches for treating residuals from non‐destructive water treatment processes, Ryan et al (2021) review electrochemical technologies such as electrocoagulation and electrooxidation. It is found that electrochemical treatment is also promising for residual streams of IX, NF, and RO processes.…”
Section: Treatmentmentioning
confidence: 99%